2016
DOI: 10.5455/medarh.2016.70.172-176
|View full text |Cite
|
Sign up to set email alerts
|

In Silico Analysis of the Potential of the Active Compounds Fucoidan and Alginate Derived from Sargassum Sp. as Inhibitors of COX-1 and COX-2

Abstract: Introduction:The enzyme cyclooxygenase (COX) is an enzyme that catalyzes the formation of one of the mediators of inflammation, the prostaglandins. Inhibition of COX allegedly can improve inflammation-induced pathological conditions.Aim:The purpose of the present study was to evaluate the potential of Sargassum sp. components, Fucoidan and alginate, as COX inhibitors.Material and methods:The study was conducted by means of a computational (in silico) method. It was performed in two main stages, the docking bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 26 publications
1
1
0
1
Order By: Relevance
“…Similarly, they reduced COX-2 mRNA expression by 82.1, 65.2, 64.1, and 70.2%, respectively, relative to the control group, in a similar manner to that of dexamethasone, which revealed a reduction of 85.2% at 40 μg/mL, where MIF1 revealed the highest inhibitory potential at all examined doses. This coincides with in silico studies of fucoidan-type sulfated polysaccharides, which turned out to be potent inhibitors of COX-1 and COX-2, and their effect may be greater than that of alginates [ 52 ]. Another study showed that Fucus vesiculosus fucoidan showed the better inhibition of both isoforms of the COX enzyme compared to indomethacin; the inhibition of COX-2 was higher than COX1 [ 53 ].…”
Section: Resultssupporting
confidence: 84%
“…Similarly, they reduced COX-2 mRNA expression by 82.1, 65.2, 64.1, and 70.2%, respectively, relative to the control group, in a similar manner to that of dexamethasone, which revealed a reduction of 85.2% at 40 μg/mL, where MIF1 revealed the highest inhibitory potential at all examined doses. This coincides with in silico studies of fucoidan-type sulfated polysaccharides, which turned out to be potent inhibitors of COX-1 and COX-2, and their effect may be greater than that of alginates [ 52 ]. Another study showed that Fucus vesiculosus fucoidan showed the better inhibition of both isoforms of the COX enzyme compared to indomethacin; the inhibition of COX-2 was higher than COX1 [ 53 ].…”
Section: Resultssupporting
confidence: 84%
“…berupa fukoidan dan alginat berpotensi menghambat enzim cyclooxygenase 1 dan 2 dalam proses peradangan. Sehingga, hal ini dapat memberikan efek yang menguntungkan terhadap proses peradangan pada kondisi patologis (Dewi, 2016). Hal ini didukung oleh hasil studi Oka dkk, bahwa kadungan senyawa bioaktif pada Sargassum sp yakni fukoidan yang merupakan polisakarida tersulfasi pada rumput laut memiliki aktivitas antimikroba kuat dalam melawan Candida albicans, S. mutans, dan P. gingivalis serta mampu menetralkan endotoksin (lipopolisakarida) dalam uji LAL (Oka et al, 2019).…”
Section: Journal Of Holistic Nursing and Health Scienceunclassified
“…The COX is an enzyme that mediates inflammation responses by prostaglandins (Dewi, 2016). The COX-2 enzyme is a significant isoenzyme in the inflammatory process but the data showed that prostanoids produced by COX-1 also play a role in inflammation (Smith & Langenbach, 2001).…”
mentioning
confidence: 99%